Prevention and inhibition of post-harvest browning in longkong pericarp using Prunus Persica resin coating during ambient storage - Narin Charoenphun; Somwang Lekjing; Karthikeyan Venkatachalam (PLoS ONE, 2025)
Background Longkong fruit is highly perishable due to rapid pericarp browning, limiting its post-harvest shelf life to less than 7 days under ambient conditions. Objectives This study evaluated the efficacy of Prunus persica resin (PPR) coatings at 1%, 2%, 3%, and 4% concentrations in preserving fruit quality over 14 days of ambient storage, with assessments conducted at two-day intervals. Methods Longkong fruits were treated with PPR coatings and stored under ambient conditions. Parameters including pericarp browning, decay rate, moisture loss, color retention, biochemical properties, and enzymatic activities were analyzed. Results PPR-coated samples exhibited superior performance compared to control samples, with higher PPR concentrations effectively mitigating pericarp browning, decay rate, and moisture loss while maintaining fruit color and biochemical properties. Control fruits became unacceptable by day 8, exhibiting a browning index exceeding 4.51 and a decay rate of 82.56%, whereas fruits treated with higher PPR concentrations (>3%) maintained lower browning indices (<3.47) and decay rates (<58.99%) by day 14. Color retention was significantly enhanced in 4% PPR-treated fruits, which maintained lightness, redness, and yellowness values, while untreated fruits exhibited severe discoloration. Moisture loss in untreated fruits reached 35.31% by day 8, whereas 4% PPR-treated fruits limited moisture loss to 20% throughout the storage period. Additionally, high concentrations of PPR coatings preserved higher total phenolic content, flavonoid levels, and antioxidant activities. PPR-coated longkong fruit effectively suppressed the activity of browning-related enzymes such as polyphenol oxidase, peroxidase, and cinnamate-4-hydroxylase, alongside reductions in membrane-degrading enzymes lipoxygenase and phospholipase D. Conclusion These findings indicate that PPR coatings, particularly at 4% concentration, effectively extend longkong fruit shelf life for up to 14 days, providing a natural, biodegradable post-harvest solution. This approach holds significant potential for reducing food waste, supporting sustainable agricultural practices, and enhancing marketability across longkong fruit supply chains, particularly benefiting small-scale farmers in tropical regions.